Towards a Typology of Cross-Channel Dramatic Borrowings: The View from the White Cliffs - Hillman, Richard (Renaissance and Reformation / Renaissance et Réforme, 2017)
Scholarship on the diverse ways in which early modern English playwrights “translated” French textual material, dramatic and otherwise, has by now accumulated enough specific instances to justify an overview of methods and results. There are few outright translations of French plays, but the field widens considerably when adaptations and appropriations of various kinds are added to the picture. It then becomes possible to identify a variety of intertextual experiences that implicate audiences in issues of genre, religion, and politics.